Pequenos cientistas: fundamentos investigativos na formação de alunos do terceiro ano do Ensino Fundamental - Guimarães, Maria Rita (Universidade Federal de São Carlos, 2025)
Science teaching in Brazil faces recurring problems that have changed little over the last few years, but when we talk about physics teaching in the early years of elementary school this becomes particularly concerning, as this period is crucial for promoting children's cognitive and scientific development. During this phase, typically spanning from the 1st to the 5th grade, it is essential to spark curiosity, encourage observation, foster investigation, and develop critical thinking skills, yet, what happens in practice during this teaching is told in another way. Therefore, this study aims to explore and analyze how physics is taught in the 3rd grade of elementary school, how it should be approached, and the challenges faced in this educational stage. A systematic bibliographic review will be conducted using scientific articles published on Google Scholar between 2019 and 2024. The study will investigate how scientific inquiry is being addressed at this age level, employing Discursive Textual Analysis methodology to evaluate the findings.
Little scientists: research foundations in the training of third-year elementary school students
Keywords: Ensino de física no fundamental I; Física nos anos iniciais; Olhar científico; Pensamento crítico; Teaching physics in elementary school I; Physics in the early years; Scientific look; Critical thinking; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM